Sites and sights of tension: cultural memory of gender and colonial power in East Asia* - Ravn Borggreen, Gunhild (Peripeti, 2023)
Taking the sculpture entitled Statue of Peace (2011) by South Korean artists Kim Seo-kyung and Kim Eun-sung as a focus point, the article explores issues of gender and colonial power in the East Asian region related to the cultural memory of “comfort women” of Korean origin. Analyses of the sculpture and its context show how geographical locations and visual representation are related to atrocities and colonial violence. It shows how the sculpture becomes both a weapon and object of violence in global solidarity.